Knowledge about sexually transmitted infections and sexual practices among young university students in the city of Cucuta (2022)
In Colombia, young people are part of the population group that is most at risk regarding their sexual health and the knowledge associated with this component, which is why we chose to describe the sexual practices and the knowledge they have regarding HIV and other STIs, consolidating an approach to undergraduate students of an HEI in northeastern Colombia from a quantitative perspective with a non-experimental design, descriptive and cross-sectional scope. The population was 2 605 students while the sampling was probabilistic with proportional allocation resulting in a sample of 525 students, considering the 12 academic programs considered for the study. Broadly speaking, the disjunctive between the knowledge associated with STIs and the sexual practices of young university students is consolidated, and strategies should be focused on sensitizing students to strengthen healthy sexual practices that reduce their risk of acquiring STIs.